Protein Paucimannosylation Is an Enriched N‐Glycosylation Signature of Human Cancers. Issue 21 (16th October 2019) - Chatterjee, Sayantani; Lee, Ling Y.; Kawahara, Rebeca; Abrahams, Jodie L.; Adamczyk, Barbara; Anugraham, Merrina; Ashwood, Christopher; Sumer‐Bayraktar, Zeynep; Briggs, Matthew T.; Chik, Jenny H. L.; Everest‐Dass, Arun; Förster, Sarah; et al.
Abstract: While aberrant protein glycosylation is a recognized characteristic of human cancers, advances in glycoanalytics continue to discover new associations between glycoproteins and tumorigenesis. This glycomics‐centric study investigates a possible link between protein paucimannosylation, an under‐studied class of human N ‐glycosylation [Man1‐3 GlcNAc2 Fuc0‐1 ], and cancer. The paucimannosidic glycans (PMGs) of 34 cancer cell lines and 133 tissue samples spanning 11 cancer types and matching non‐cancerous specimens are profiled from 467 published and unpublished PGC‐LC‐MS/MS N ‐glycome datasets collected over a decade. PMGs, particularly Man2‐3 GlcNAc2 Fuc1, are prominent features of 29 cancer cell lines, but the PMG level varies dramatically across and within the cancer types (1.0–50.2%). Analyses of paired (tumor/non‐tumor) and stage‐stratified tissues demonstrate that PMGs are significantly enriched in tumor tissues from several cancer types including liver cancer ( p = 0.0033) and colorectal cancer ( p = 0.0017) and is elevated as a result of prostate cancer and chronic lymphocytic leukaemia progression ( p < 0.05). Surface expression of paucimannosidic epitopes is demonstrated on human glioblastoma cells using immunofluorescence while biosynthetic involvement of N ‐acetyl‐β‐hexosaminidase is indicated by quantitative proteomics. This intriguing association between protein paucimannosylation and human cancers warrants further exploration to detail the biosynthesis, cellular location(s), protein carriers, and functions of paucimannosylation in tumorigenesis and metastasis.